Community involvement tools for advancing sustainability - Griswold, Wendy; Steichen, Marie (Kansas State University, 2009)
There are many community involvement and educational tools that can be utilized to support and facilitate the individual, group and institutional transformations required for the development of sustainable communities. The tools to be presented in this workshop include Empowerment Evaluation, transformative learning, service learning, public issue facilitation, and appreciative inquiry. These tools provide mechanisms to build capacity, facilitate critical thinking and action, engage participants, and help stakeholders reach consensus and make decisions. The power of these tools lie in their participatory approaches and the different kinds of conversations each of these processes engenders. Focusing on authentic engagement through public dialogue, transformation through education and reflection, community betterment through Service-Learning, and research and evaluation through collaborative processes, these tools have the ability to move individuals and communities to a higher level of functioning for the community good. This presentation will introduce these tools and provide guidance on how they could be used in a variety of settings to advance sustainability.
Keywords: Sustainable communities; Empowerment evaluation; Transformative learning; Service learning; Public issue facilitation; Appreciative inquiry